The right of consultation to the peasant communities on the exploitation of natural resources in their communal lands: comments to the judgment of the Peruvian Constitutional Court in Docket N ° 03343-2007-PA / TC - Vinatea Medina, Ricardo (2009)
The decision contained in Docket N° 3343-2007-PA/TC is based on formal issues and not on issues tangential to the specific case, which prevents a binding precedent from being rendered in order to make effective the rights of native communities to an ethnic and cultural identity, the right to previous consultation, and the right to participate in the execution and evaluation of policies directly affecting them.